Ameliorative impact of herbal formulation —Majoon-Dabeed-ul-ward and Sharbat-e-Deenar against CCl4 induced liver toxicity via regulation of antioxidant enzymes and oxidative stress. Issue 5 (1st September 2022) - Shakya, Arvind Kumar; Sharma, Neetu; Bhadauria, Monika; Nirala, Satendra Kumar; Shrivastava, Sadhana; Shukla, Sangeeta
Abstract: Polyherbal Unani formulations have been used in the treatment of liver diseases for a long time. (Ibrahim M, Khaja MN, Aara A, Khan AA, Habeeb MA, Devi YP, Narasu ML, Habibullah CM. Hepatoprotective activity of Sapindus mukorossi and Rheum emodi extracts: in vitro and in vivo studies. World J Gastroenterol . 2008:14 :2566–2571.) The aim of the present study was to investigate comparative hepatoprotective potential of Majoon-e-Dabeed-ul-ward (MD) and Sharbat-e-Deenar (SD) against CCl4 induced subchronic hepatic toxicity. In vivo study, albino rats were divided into 5 groups. Group I was control; Group II was experimental control treated with CCl4 (0.15 mL/kg, i.p. for 21 days); Groups III–IV treated with SD (2 mL/kg, p.o.) and MD (1, 000 mg/kg, p.o.) for 5 days following CCl4 intoxication as in group 2 respectively; and Group V was positive control treated with silymarin (50 mg/kg, p.o.). In vitro hepatoprotective activity of SD and MD (25, 50, and 100 μg/mL) was assessed by SRB assay and flow cytometry analysis. CCl4 exposure significantly elevated the release of hepatic enzymes i.e. AST, ALT, LDH, and SALP in serum and lipid peroxidation in liver tissue which all these parameters were reversed after SD and MD administration. Therapy for 5 days also normalized the levels of antioxidant enzymes i.e. catalase, SOD, GPx, GR, tissue GSH, and aniline hydroxylase in CCl4 treated group. DNA damage and histological alterations caused by CCl4 were restored towards normal group. In vitro study showed protective effect of SD and MD against CCl4 treated HepG2 cell lines and rat hepatocytes. The results suggested that MD has a significant hepatoprotective potential and regulatory effect on oxidative stress than SD against CCl4 induced hepatotoxicity, and that this effect may be related to its antioxidant activity.